Utilization of Tannins with Various Polymers for Green-Based Active Packaging: A Review - Agrippina, Fidela Devina; Ismayati, Maya; Hidayati, Sri; Pratama, Bima Putra (Jurnal Sylva Lestari, 2024)
Tannin is a major polyphenolic secondary metabolite widely distributed in the forestry sector and can be added to polymer matrices to manufacture bioactive films for food packaging. Tannins have functional properties as antioxidants, antibacterial, and anti-inflammatories. Tannins are classified into two types, namely condensed tannins and hydrolyzable tannins. Tannins have been used primarily in food, wood, leather, pharmaceutical, and other industries. In the food industry, tannins are used to develop food packaging, preservation, and the function of the food industry. Tannin molecules have the advantage of combining with polymers or polymer surfaces, for example, synthetic polymers, biopolymers, and micro- and nano-sized fibers, which will form new products whose physical and chemical properties increase in functional properties because of the presence of hydrophilic and nucleophilic groups. Combining tannins with a polymer can be done by one-step reactive extrusion, layer by layer, dynamic vulcanization, acetylation, and in situ extraction methods. This paper describes general information about tannins, followed by applications using tannins, tannin-based hybrid materials, and methods of combining tannins with a polymer for food packaging purposes. Keywords: active packaging, bioactive film, polymer, secondary metabolite, tannins